Penerapan Penjatuhan Hukuman Pidana terhadap Percobaan Pembunuhan Berencana yang Dilakukan Oleh Pelaku : (Studi Putusan Nomor 150/Pid.B/2020/PN JKT.UTR & Putusan Nomor 1607/Pid.B/2019/PN JKT. UTR) - Jhon Hausen Sibuea; Boedi Prasetyo (Jurnal Hukum Lex Generalis, 2024)
Premeditated murder is one of the social symptoms that still occurs in many societies. The perpetrator of premeditated murder wants the loss of life of another person. However, the loss of life of others does not materialise, so the perpetrator is charged with attempted premeditated murder. This research discusses how the responsibility of the perpetrator of attempted premeditated murder and how the application of criminal offences against attempted premeditated murder. This research examines Decision Number 150/Pid.B/2020/PN JKT.UTR and Decision Number 1607/Pid.B/2019/PN JKT. UTR. This research is normative legal research conducted by examining library materials or secondary data. This research uses case approach method and statutory approach. The results showed that the perpetrator or defendant of attempted murder can be charged with criminal responsibility if the criminal act has been proven, has the ability to be responsible based on the provisions of Article 44 paragraph (1) to 1 of the Indonesia Criminal Code, and there are no reasons for criminal erasure which can be in the form of excuses and justification reasons. The imposition of criminal sanctions for the criminal offence of attempted premeditated murder is a maximum penalty of 15 (fifteen) years in accordance with the provisions of Article 53 paragraph (4) of the Indonesia Criminal Code. The punishment of the perpetrator of attempted premeditated murder as in Decision Number 150/Pid.B/2020/PN JKT.UTR and providing the means to commit attempted premeditated murder in Decision Number 1607/Pid.B/2019/PN JKT.UTR is in accordance with what has been regulated in Article 53 paragraph (4) of the Indonesia Criminal Code, the imposition of probationary punishment if the crime punishable by death or life imprisonment is a maximum of 15 (fifteen) years. When viewed from the verdict in the case of the two defendants, it is in accordance with the provisions by not exceeding the maximum limit of 15 (fifteen) years.